Modern Towed Systems: New developments of multipurpose platforms - Haag, Christian (2016)
Towed systems for the inspection of trawl netshave been in use for several decades. Mariscope got into the game with thedevelopment of the Magnus Tow for the German Bundesanstalt für Fischrei inHamburg in 1995. This system used Magnus rotors instead of propellers toposition itself in the trawl net during the trawl. This system was a hybridsince propulsion was used to position the unit at the right place during theoperation within the net. The company has developed a new hybrid system withoutrotors: the Observer III. The first application is a standalone system to beattached inside a trawl net during operation. Here, the position is fixed, butthe system needs to automatically start and stop recording and control thelights and other sensors in order to reduce power consumption.